Donor Herding and Domestic Debt Crisis - Chirwa, Ephraim (IMF Working Papers; Working Paper ;, 2006)
This paper presents a new model based on the loan-pushing model by Basu (1991) to show how a domestic debt crisis can occur in a low-income country following donor herding. The model focuses on the rational herding behavior of donors due to payoff and information externalities. Although there are many theoretical models on herding behavior, these models have not formally considered the relationship between donor herding and domestic debt crisis in a low-income country. This paper is an attempt to fill this gap. The paper shows that due to donor herding behavior a domestic debt crisis can occur once the actual debt level is above the desirable one.